Correlates of Sleep Disturbance Among Peoples Living in Jeju Island, Korea - Moon-Doo Kim (BJPsych Open, 2025)
Aims: Individuals dissatisfied with their sleep are more likely to seek medical help, to report daytime impairment functioning, and to be diagnosed with a sleep or a mental disorder However, none of the previous studies has examined the relative importance of the various factors correlated to sleep disturbance. This study aims to investigate the prevalence of sleep disturbance and to find the associated factors contributing to sleep disturbance in the general population of Jeju Island, the largest island in the part of South Korea.